Assessing green practice behavior: The mediating roles of normalization and behavioral intention - Wong, Ling Chai (2019)
Given the findings from previous studies, assessing green practice behavior proved to be a challenging task because the intention claimed does not always reflect actual behavior. In order to solve this problem, normalization is proposed. This method provides a systematic how-to guideline for consumers to carry out green practice in their daily routine. The current study specifically proposed green practice behavior in the usage of smartphones following the evolution of regular mobile phones into smart multi-functional mobile computers that led to a serious Abnormal Battery Drain issue. Normalization on various aspects of a smartphone such as its battery consumption before sleep, internet connection, charging process, and the use of power saving mode is imperative to be taken into consideration in practicing a green on mobile phone. However, very few studies have been conducted focusing on this issue. Therefore, the current study examined the factors that affect consumers’ behavioral intention towards smartphone’s green practice, inspected the relationship between consumers’ behavioral intention and the actual behavior of smartphone’s green practice. Investigated the relationship between consumers’ behavioral intention and normalization of smartphone’s green practice, and the relationship between normalization and the actual behavior of smartphone’s green practice. Simultaneously, the current study also investigated the impact of behavioral intention and normalization as the mediators of consumers’ actual behavior of smartphone’s green practice. In terms of data collection, a complete set of data received from 442 respondents via snowball sampling method was analyzed using Partial Least Square-Structural Equation Modelling approach. The results confirmed that a positive signif icant relationship exists between attitude, subjective norm, and perceived behavioral control on behavioral intention towards smartphone’s green practice. T he next section of the survey that concerned with the behavioral intention has a positive significant impact on normalization and consumers’ actual behavior of smartphone's green practice. Furthermore, the role of normalization and behavioral intention as mediator was also confirmed in the current study. Discussions on the findings, implication and direction for future research are also presented in the final section of the study.